Delamination migration in CFRP laminates under mode I loading. (12th April 2020) - Ramji, Amit; Xu, Yigeng; Yasaee, Mehdi; Grasso, Marzio; Webb, Philip
Abstract: This paper focuses on the effect of interfacial fibre orientation and interleaved veil on the delamination migration of carbon fibre reinforced polymer laminates under Mode I loading. Double cantilever beam specimens with midplane interfacial fibre orientations of 0/0, 90/90, 0/90, 0/45 and 90/45 were tested under two conditions: one with interleaved thermoplastic polyphenylene sulfide veil at the midplane and one without. Results show that, except for the 0/0 configuration, all other orientations exhibit varying levels of migration associated with the interfacial fibre orientation and veil interleaving. The apparent fracture toughness determined with the modified compliance calibration method is closely related to the delamination migration and hence a structural energy dissipation measure dependent on interfacial fibre orientation and the interleaved veil. Distributions of the fibre and matrix materials around the delamination front are found to be closely related to the delamination migration behaviour along its path. The experimental observation and rationalisation presented in this paper provide further knowledge regarding delamination migration and its correlation to the apparent fracture toughness, which is of direct relevance to the damage tolerance design of laminated composite components.